The Effect of Multipurpose Murabahah Financing on The Development of Micro, Small and Medium Enterprises - Rika Umbaiyani Ritonga; Sugianto; Tuti Anggraini (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2024)
Micro, small and medium enterprises are one of the spearheads of the country's economic development that require special attention to continue to develop them. This research aims to determine the effect of multipurpose murabahah financing on the development of micro, small and medium enterprises in Kota Baru Marelan with a case study at Bank SUMUT Syariah KCP Kota Baru Marelan. This research uses quantitative methods with a sample of 30 respondents. Sampling is done using techniquerandom sampling. The analysis used in this research is simple linear regression analysis, which is used to find out how much influence the independent variable has on the dependent variable. The results of the research on the t test obtained a significance value of 0.000, valueUnstandardized Coefficients as much as 0.675, Standardized Coefficients as much as 0.669, on the coefficient of determination (R2) the R-Square value obtained is 0.448 or 44.8%. So it can be concluded that the multipurpose murabahah financing carried out by Bank SUMUT Syariah KCP has a significant influence on the development of micro, small and medium enterprises in Kota Baru Marelan in a positive direction. The murabahah financing variable influences the development of MSMEs by 44,8%, then the remaining 55,2% is influenced by other variables outside this research.